2014
DOI: 10.4269/ajtmh.14-0216
|View full text |Cite
|
Sign up to set email alerts
|

Brain MRI of Children with Retinopathy-Negative Cerebral Malaria

Abstract: Abstract. Our goals were to understand the brain magnetic resonance imaging (MRI) findings in children with retinopathy-negative cerebral malaria (CM) and investigate whether any findings on acute MRI were associated with adverse outcomes. We performed MRI scans on children admitted to the hospital in Blantyre, Malawi with clinically defined CM. Two hundred and seventeen children were imaged during the study period; 44 patients were malarial retinopathy-negative; and 173 patients were retinopathy-positive. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The precise pathological processes and mechanisms leading to cerebral malaria are still unclear, hampering the development of efficacious treatments. Typically, cerebral malaria is accompanied by malaria retinopathy, which is considered as an early symptom for most forms of cerebral malaria 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The precise pathological processes and mechanisms leading to cerebral malaria are still unclear, hampering the development of efficacious treatments. Typically, cerebral malaria is accompanied by malaria retinopathy, which is considered as an early symptom for most forms of cerebral malaria 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies showed that 79.7% (Postels et al, 2014) and 54.6% of the Malawian CM patients had retinopathy (White et al, 2009). Moreover, another prospective cohort study of the retinopathy-positive CM patients identified 31.8% to have neurological sequelae such as epilepsy and behavioural disorders (Kampondeni et al, 2013) and surprisingly, some adverse neurological outcomes were also observed in retinopathy-negative CM patients (Postels et al, 2014). Meanwhile, the retinopathy-positive and retinopathy-negative CM in Malawian children could be distinguished by the level of plasma concentrations of the parasite histidine rich protein 2 (pHRP2) which is a known predictor of intracerebral parasite sequestration (Seydel et al, 2012).…”
Section: Falciparum Malaria: Life Cycle and Clinical Epidemiology Of mentioning
confidence: 89%
“…In a prospective study of 326 patients with complicated malaria, 278 (85.3%) patients were reported to have CM and among them, 170 (61.15%) had some degree of retinopathy which was strongly associated with subsequent death in the CM patients (Beare et al, 2004). However, other studies showed that 79.7% (Postels et al, 2014) and 54.6% of the Malawian CM patients had retinopathy (White et al, 2009). Moreover, another prospective cohort study of the retinopathy-positive CM patients identified 31.8% to have neurological sequelae such as epilepsy and behavioural disorders (Kampondeni et al, 2013) and surprisingly, some adverse neurological outcomes were also observed in retinopathy-negative CM patients (Postels et al, 2014).…”
Section: Falciparum Malaria: Life Cycle and Clinical Epidemiology Of mentioning
confidence: 99%
“…Several studies provided evidence that CM could be better defined clinically using fundoscopy to identify CM-specific changes in the retina that mirror changes in the brain vasculature that correlate with disease (19)(20)(21)(22). However, recent studies evaluating a variety of clinical parameters suggest that fundoscopy may not provide a binary parameter of CM but rather may reflect a spectrum of CM disease presentation, with severe retinal changes indicating late or more severe stages of CM (23)(24)(25).…”
mentioning
confidence: 99%